Respuesta :

Answer:

3x^6 - 4x^5 + 2x^4

Step-by-step explanation:

Given

-5x^4 ( -3x^2 + 4x - 2)

Step 1 : open the bracket with -5x^4

-5x^4 * -3x^2= 15x^6

Hint: - * - = +

x^4 * x ^2 = x^ 4+2 = x^6

-5x^4 * + 4x = - 20x^5

Hint: - * + = -

x^4 * x = x^4 + 1 = x^5

(x is always raise to the power of 1 but we don't write it or less it is greater than 1 e.g. 2 , 3 ,4, ..........)

-5x^4 * -2 = 10x^4

Hint: - *- = +

Let's combine the answers

15x^6 - 20x^5 + 10x^4

We can look for a factor that can go through as in that can divide all without a reminder

Factors of

15 - 3 * 5

1 * 15

20 - 4 *5

2 *10

1 * 20

10 - 2*5

1 * 10

Since the factor of 5 is common in all, so we are using 5 to divide through

15x^6 - 20x^5 + 10x^4

Using 5 to divide through

15x^6 / 5 - 20x^5 / 5 + 10x^4 / 5

= 3x^6 - 4x^5 + 2x^4

ACCESS MORE